Failure Mode and Effect Analysis: A Technique to Prevent the Risk of SARS-COV-2 Infectionin A Retrocession Unit - Esso Eric Valery Latt; Youssef Moutaouakkil; ZidaneQriouet; YassineAtbib; YasminaTadlaoui; Jamal Lamsaouri; YassirBousliman (Institute of Medico-legal Publications Pvt Ltd, 2021)
Securing healthcare workers and patients against the severe acute respiratory syndrome coronavirus 2 (SARSCoV-2) infection/transmission, require the development of new tools and methods. Several laboratories have started recently clinical trials to develop vaccines and drugs, however these solutions require more time to evaluate and validate them. As an alternative and in order to stop the spread of SARS-CoV-2 infection, our objective is to implement preventive and corrective actions to reduce the infectious/transmission risk of SARS-COV-2 during hospital retrocession, using the failure mode effect analysis (FMEA) method. The criticality of each failure mode was assessed by calculating the criticality index (CI). The obtained data showed 12 fault modes with a total criticality index (CI) of 480, two acceptable risks, four significant risks and six critical risks. Ten risks were identified as priorities (CI > 15): four related to patient reception, two related to personnel, two during dispensation, one related to the end of dispensation and the last related to traceability. These risks were corrected by improvement actions proposed by FMEA and then re-evaluated effectively.This study assessed the feasibility and relevance of the use ofFMEA in the hospital retrocession dispensing process related to the infectious/transmission risk of SARS-CoV-2.Finally, FMEA seems to be an effective method to reduce the infectious/transmission risk of SARS-COV-2 during hospital retrocession.